Influence of improved production technologies on productivity and economics of sunflower (Helianthus annuus L.) in Nichabanadhi sub-basin of Tamil Nadu: INFLUENCE OF IMPROVED PRODUCTION TECHNOLOGIES ON PRODUCTIVITY OF SUNFLOWER - M PARAMASIVAN; A SELVARANI (Journal of Oilseeds Research, 2016)
Two hundred and fifteen on-farmdemonstrations on improved production technology (IPT) for sunflower were carried out in 175 hectares of farmer’s fields in Sankarankovil, Vasudevanallur and Kuruvikulam blocks of Tirunelveli district of Tamil Nadu from 2009-10 to 2011-12. The results revealed that the adoption of improved production technology favorably influenced growth, yield and economics ofsunflower. Higher mean net returns of Rs. 34,818/ha with a benefit: cost ratio of 2.66 was obtained with improved production technologies in comparison to farmer’s practice (mean net returns of Rs. 19,385/ha and benefit: cost ratio of 2.05). Adoption of IPT gained an additional net profit of Rs. 15,433/ha as compared to traditional method of sunflower cultivation.